Tanggungjawab Perdata Dokter Dalam Kelalaian Medis Pada Tindakan Operasi Medik Terkait Persetujuan Tindakan Medis (Informed Consent) - Hendri Farozah (Lex Stricta : Jurnal Ilmu Hukum, 2024)
The existence of informed consent plays a fundamental role in the legal relationship between doctors and patients, serving as both the basis for the legitimacy of medical actions and a legal safeguard for both parties. This study employs a normative juridical method with secondary data sources to examine two main issues: the position of informed consent in relation to doctors’ civil liability and the form of accountability in cases of medical negligence during surgical procedures. The findings indicate that informed consent functions as a defensive mechanism for doctors against potential patient lawsuits while ensuring a sense of security in the delivery of medical care. In cases of negligence, doctors may be held civilly liable for material damages, including medical expenses and loss of income, as well as immaterial damages such as pain, anxiety, and emotional distress. Such claims can be brought before the District Court, as the doctor’s actions may contravene principles of propriety, diligence, and prudence, as regulated under Articles 1239, 1365, and 1366 of the Indonesian Civil Code.